Sub-Governorate of Zakho in the Ottoman Administrative Divisions 1842- 1914 - Hassan, Nizar A. (Humanities Journal of University of Zakho, 2017)
Zakho city was a key Kurdish town at the very critical time in the light of its geostrategic position, which is situated in the borders of Mosul between the states of Iraq, Turkey and Syria. Also, the geographical position of this city made it a big economic center in addition it’s a main door of dealing trade between Kurdistan and foreign world. Although , it is a wealthy in agriculture and metallic revenues. On the other hand, Zakho is an ancient town and it’s a center of crucial civilization in the Badhdinan areas. The history of this city has not been taken into an account that connected its past to its recent position. Hence, this study is used some original Ottoman documents and official Ottoman statements, which are showed the development of Zakho position in the Ottoman administration divisions from the end of Bahdinan emirate in 1842 to the British control over south Kurdistan and Zakho town in 1918, likewise, sheet light on the Zakho position in banner (wilayat), districts (Sanjaks), establishing of sub-governorate of district of Zakho and other sub-district which were belonged to Zakho county.